Exact Equations
Additional Examples
- We write the equation in the standard form,
M dx + N dy = 0 . $$ (-10xy - 12x - 5y - 4) dx + (-5x^2 - 5x - 24) dy = 0 $$ - We test for exactness. $$\frac{\partial}{\partial y}\left(-10xy - 12x - 5y - 4\right) = -10x - 5 = \frac{\partial}{\partial x}\left(-5x^2 - 5x - 24\right) $$ so the equation is exact.
- Write the partial differential equations. $$ \begin{align} \frac{\partial F}{\partial x} &= -10xy - 12x - 5y - 4\\ \frac{\partial F}{\partial y} &= -5x^2 - 5x - 24 \end{align}$$
- Integrate the first partial differential equation. $$ F(x,y) = \int (-10xy - 12x - 5y - 4)\,\partial x = -5x^2y - 6x^2 - 5xy - 4x + C(y) $$
- Integrate the second partial differential equation. $$ F(x,y) = \int (-5x^2 - 5x - 24)\,\partial y = -5x^2y - 5xy - 24y + \tilde{C}(x) $$
- Equate the expressions for F(x,y). Matching the expressions up, we find $C(y) = -24y$ and $ \tilde{C}(x) = -6x^2 - 4x. $ So $$ F(x,y) = -5x^2y - 6x^2 - 5xy - 4x - 24y. $$
- The solution is $F(x,y) = K.$ $$ -5x^2y - 6x^2 - 5xy - 4x - 24y = K $$
If you have any problems with this page, please contact bennett@math.ksu.edu.
©2010, 2014 Andrew G. Bennett